2019
DOI: 10.3390/dj7030078
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and Bond Strength of Universal Dental Adhesives with Co-Cr Alloy and Zirconia

Abstract: The aim of this study was to evaluate (a) the reactivity of six universal dental adhesives with polished cobalt-chrome (Co-Cr) alloy and zirconia (3Y-TZP) surfaces; and (b) to assess the shear bond strength (SBS) of a resin composite with polished and alumina-blasted surfaces as mediated by these adhesives. The products tested were Adhese Universal (AD), All-Bond Universal (AB), Clearfill Universal Bond (CB), G-Premio Bond (GP), Prelude One (PO) and Scotchbond Universal (SB). The reactivity on polished substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…As shown in Table 7, the pure Ti substructure obtained by casting manufacturing [28] present lower adhesion values to resin cement even if methods were applied to improve the adhesion process by sandblasting with alumina and application of metal primer (7.5 MPa) or engraved with hydrochloric acid and application of metal primer (6.1 MPa). The shear bond strength of pure Ti adhesion to GC Fuji [29] was approximately the same as the values recorded in this study (8.5 MPa) and compared to resin cement (Panavia and Rely X U200) they increased considerably (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). The same CAD-CAM milling technique was used by Korkmaz [17] to obtain a Ti6Al4V substrate.…”
Section: Discussionsupporting
confidence: 81%
“…As shown in Table 7, the pure Ti substructure obtained by casting manufacturing [28] present lower adhesion values to resin cement even if methods were applied to improve the adhesion process by sandblasting with alumina and application of metal primer (7.5 MPa) or engraved with hydrochloric acid and application of metal primer (6.1 MPa). The shear bond strength of pure Ti adhesion to GC Fuji [29] was approximately the same as the values recorded in this study (8.5 MPa) and compared to resin cement (Panavia and Rely X U200) they increased considerably (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). The same CAD-CAM milling technique was used by Korkmaz [17] to obtain a Ti6Al4V substrate.…”
Section: Discussionsupporting
confidence: 81%
“…Regarding the GSUNIVERSAL group that reached the highest adhesion values, both immediately and after aging, these results only confirm what was reported by researchers such as Nima, et al (1), Papadogiannis, et al (16), Jamel, et al (18), Al-Heou and Swed (29), and Bankoğlu, et al (30). The GSUNIVERSAL group was sandblasted and immediately afterwards silane and a universal adhesive (Single Bond Universal®, 3M.…”
Section: Discussionsupporting
confidence: 62%
“…Indeed, our study only confirmed what was reported by Marchesi, et al (35), who found that after having kept the samples in water for one-year, low values were obtained when using a universal adhesive system, since the stability of the interface gets lost over time. In the long term, 10-MDP can absorb moisture due to the phosphate radical, which would cause a degradation of the polymer network and consequently, a reduction in the bond strength of the materials (16,36,37). In any case, in our study, despite the fact that the initial values decreased with aging, they are still interesting and good.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In addition to the various monomers they contain, these resins are also used to bond ceramic, zirconium, or metal substructures with resin-containing materials. [ 27 ] In particular, previous studies indicated that 10-methacryloxydecyl dihydrogen phosphate (MDP) monomer-containing resins increase the bond of titanium with resin materials. [ 25 26 27 28 ] This study used a UB containing a three-dimensional self-reinforcing monomer (3D-SR) monomer with phosphate groups similar to the MDP monomer.…”
Section: Discussionmentioning
confidence: 99%